FORMATION OF WINTER WHEAT YIELD DEPENDING ON SOWING DATES - Lykhochvor , В.; Aliokhin , В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The influence of sowing dates on the yield of winter wheat, specifically the RZhT Reform variety, was studied, including very late sowing dates following sugar beet cultivation. The examined sowing dates were spaced 20 days apart: September 10 and 30, October 20, November 10 and 30, and December 20. Sowing rates were calculated as follows: for September, it was 3.0 million seeds per hectare; for October, 5.5 million seeds per hectare; for November, 7.0 million seeds per hectare; and for December, 7.5 million seeds per hectare. The results indicated that field germination decreased for later sowing dates: in October, it ranged from 89.2% to 86.1%; in November, it was 81.4%; and in December, it decreased to 76.5%. Winter hardiness varied between 98.7% and 95.0%. Plant survival rates were between 92.4% and 88.8%, also showing a slight decline with later sowing dates. Interestingly, plant density was higher at later sowing dates, recorded at 509 to 455 plants per square meter, which can be attributed to the increased seeding rates. The density of productive stems was highest at the September and October sowing dates, reaching 590 to 630 plants per square meter. In November, this density decreased to between 568 and 535 plants per square meter, and in December, it further declined to 500 plants per square meter. The productive tillering coefficient was highest in September, ranging from 2.55 to 3.33. However, for November and December sowing dates, the plants did not reach the beginning of tillering, resulting in a productive tillering coefficient close to one (1.10 to 1.14). The number of spikelets per ear remained stable across all sowing dates, ranging from 16.1 to 17.4 spikelets. The maximum number of grains per ear (48 grains) was recorded for the September 30 sowing date. The mass of grain per ear was consistently high across all variants; for the September 30 and October 20 sowing dates, it measured 1.61 and 1.60 grams, respectively, while it decreased to 1.55 grams in November and December. The highest grain yield of 10.14 tons per hectare for winter wheat in the Western Forest-Steppe of Ukraine was achieved with the September 30 sowing date. In November, the yield decreased by 1.34 tons per hectare compared to the September 30 date, and by 1.85 tons per hectare in December – a decline of 2.39 tons per hectare. Based on this study, the optimal sowing dates for the RZhT Reform variety of winter wheat in the Western Forest-Steppe region are from September 20 to October 10. Given the conditions of global climate change, it is feasible to achieve a yield of 7 to 8 tons per hectare when sowing in November or December. For a target yield of 10 tons per hectare, the optimal combination of structural elements should include approximately 630 productive stems per square meter and a grain mass per ear of 1.61 grams.